Information Rigidity and the Expectations Formation Process : A Simple Framework and New Facts - Coibion, Olivier; Gorodnichenko, Yuriy (Washington, D.C. : International Monetary Fund, 2012)
We propose a new approach to test the full-information rational expectations hypothesis which can identify whether rejections of the arise from information rigidities. This approach quantifies the economic significance of departures from the and the underlying degree of information rigidity. Applying this approach to U.S. and international data of professional forecasters and other agents yields pervasive evidence consistent with the presence of information rigidities. These results therefore provide a set of stylized facts which can be used to calibrate imperfect information models. Finally, we document evidence of state-dependence in the expectations formation process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet